2013
DOI: 10.1002/bmc.3016
|View full text |Cite
|
Sign up to set email alerts
|

Application of TLC, HPLC and GC methods to the study of amino acid and peptide enantiomers: a review

Abstract: Amino acids are very important organic compounds in nature. The biological activity of amino acids depends mainly on their stereoisomeric configuration (d- or l-). Thus, the stereochemical analysis of amino acids and peptides is an important aspect of their characterization. Owing to the increasing role of amino acid configuration in biomedical and pharmaceutical studies, numerous analytical methods have been described in the literature. Among a wide range of analytical techniques available for the steroselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 117 publications
0
48
0
4
Order By: Relevance
“…In fact, in spite of the continuous improvement and upgrade of several chromatographic [1] and electrodriven techniques [2] that allow not only the recognition but also the enantioseparation of L-and D-AAs, there is still an increasing demand of simple and ready to use kit for rapid and sensitive detection of D-amino acids. In fact, studies in the last decades [3,4] have shown that D-AAs are widely present in the tissues of higher organisms, including humans, either as products of the vital activities of endogenous flora or during spontaneous racemization of L-AAs in the structure of polypeptides during aging [5,6], as well as endogenous active substances and biomarkers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in spite of the continuous improvement and upgrade of several chromatographic [1] and electrodriven techniques [2] that allow not only the recognition but also the enantioseparation of L-and D-AAs, there is still an increasing demand of simple and ready to use kit for rapid and sensitive detection of D-amino acids. In fact, studies in the last decades [3,4] have shown that D-AAs are widely present in the tissues of higher organisms, including humans, either as products of the vital activities of endogenous flora or during spontaneous racemization of L-AAs in the structure of polypeptides during aging [5,6], as well as endogenous active substances and biomarkers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral discrimination has attracted considerable attention in academia and industry, especially in biological, pharmaceutical and agrochemical fields [1][2][3]. This interest is attributed to heightened awareness that any compounds of biological and pharmaceutical interest are chiral and their enantiomers often exhibit different bioactivities and biotoxicities.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic analysis of AAs has recently been reviewed [7]. Although AA analysis using gas chromatography (GC) with flame-ionization or electron-capture detection has been described, currently GC-MS is becoming more and more wide-spread.…”
Section: Introductionmentioning
confidence: 99%